Challenges in Agile Transformation Journey: A Qualitative Study - Reginaldo, Fabio; Santos, Gleison (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Context: The agile transformation of an organization is influenced by different factors that can hinder the initiative's success, such as lack of adaptation of agile practices to the organizational context, selection of agile alternatives without using appropriate criteria, and lack of knowledge of the associated challenges. Not all organizations properly recognize these factors. Objective: We aim to identify challenges that can impact the success of agile transformations initiatives. Method: We executed a qualitative study using thematic analysis. We interviewed key persons in charge of the agile journey in four Brazilian organizations. Results: We identified 26 challenges in five dimensions: People, Organizational Culture, Processes, Scalability, and Technology. Among the main challenges are inadequate training, communication difficulties, a culture conflicting with agile values, incompatible organizational structure, and lack of a process to guide the transition. Conclusion: The results suggest urgency in the treatment of agile adoption as a contextualized project for organizational improvements.